2020
DOI: 10.1111/ane.13242
|View full text |Cite
|
Sign up to set email alerts
|

Distinct non‐motor features of essential tremor with head tremor patients

Abstract: Background There have been few comprehensive scale studies on the non‐motor symptoms (NMS) of patients with essential tremor (ET) with head tremor (ETh) and those with ET without head tremor (ETol). We aimed to explore the motor symptoms and NMS of these two subgroups. Methods We enrolled 199 patients with ET (125, ETol; 74 ETh) and 132 healthy controls. We evaluated motor symptoms using the Fahn‐Tolosa‐Marin Tremor Rating Scale (TRS) and NMS using the Non‐Motor Symptom Scale (NMSS). We compared NMSS scores an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…In our previous study, we explored the correlation between affective symptoms and MT, which revealed MT to be associated with anxiety and depression symptoms in ET 22 . Recently, Bologna et al 9 reported patients with head tremor to have a higher occurrence of psychiatric disorders, and Peng et al 23 showed that ET patients with head tremor had a higher incidence of memory and affective disorders than patients without head tremor. Several mechanisms could explain the pronounced mental symptoms observed in ET patients with MT.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we explored the correlation between affective symptoms and MT, which revealed MT to be associated with anxiety and depression symptoms in ET 22 . Recently, Bologna et al 9 reported patients with head tremor to have a higher occurrence of psychiatric disorders, and Peng et al 23 showed that ET patients with head tremor had a higher incidence of memory and affective disorders than patients without head tremor. Several mechanisms could explain the pronounced mental symptoms observed in ET patients with MT.…”
Section: Discussionmentioning
confidence: 99%
“…Essential tremor was defined as an Axis 1 tremor syndrome with "isolated tremor syndrome of bilateral upper limb action tremor" of "at least 3 years' duration" in the "absence of other neurological signs, such as dystonia, ataxia, or parkinsonism". "Essential tremor plus" was adopted to describe tremor with the characteristics of ET as well as "additional neurological signs of uncertain significance" [1], in order to accommodate the additional movement disorders and non-motor symptoms increasingly described in ET patients [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Essential tremor patients with jaw tremor have more severe clinical symptoms and more widely distributed tremor than patients without it. Essential tremor patients with head tremor may be also regarded as a more severe clinical subtype (66). This manifestation combined with the hypothesis that the evolution from ET to PD is caused by the spread of Lewy bodies in the cerebellothalamocortical circuit leads us to speculate that there may be some relationship between jaw tremor and subsequent PD.…”
Section: Tremormentioning
confidence: 99%